(untitled) (Journal of Business and Technology (Dhaka), 2012)
Banks are the financial institutions that provide different services through depositproducts, loan-products, etc. Debit card is one of the prominent card services related to deposit-products, which offers customers 24- hours banking access, such as cash withdrawal, purchasing of goods and services, etc. But sometimes customers are to face many problems i.e. non-availability of Taka, network problem, lack of desired value denominated notes and so on. This paper reveals how much debit card users of banks in Bangladesh are satisfied. Findings reveal that on an average debit card users are satisfied. Regarding availability of Taka in the ATM booth, users are most satisfied and regarding network service users are least satisfied. By improving network service, providing receipt after transactions and solving of problems promptly, banks can make their debit card users fully satisfied. Key words: Debit card; Customer satisfaction; Electronic banking. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9937 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 88-103